Adapter les pratiques aux valeurs, adapter les valeurs aux pratiques : compensation et conciliation des habitants du périurbain pour une mobilité durable - Georges-Henry Laffont; Denis Martouzet (Développement Durable et Territoires)
This text, clearly focus on the universe of individuals practices sense bases on the hypothesis that adaptation is the process used in the face of durability (french translation of sustainability). Everybody negotiates with it sown values according to the situation in which it is and which it represents itself. Using a quantitative approach (a measure of the movements) and a qualitative one (an interview that put people in front of the cartographic reality of their mobility via a logger-GPS) allows us to reach the justifications of practices. These are analyzed in the ell of the durability and the status that is confer to it by the investigated people, between standards, practical theory or new labels of former practices. Two modes of negotiation are so highlighted: the conciliation between the individuals values and their implementation “in practice”; the compensation between practices which do not answer the values and the others who answer it, allowing a globally positive intuitive balance assessment of the least acceptable for people. By the way, relationship with durability is sketched through five behavioral figures.